Occult hypoperfusion and changes of systemic lipid levels after severe trauma: an analysis in a standardized porcine polytrauma model. - Kumabe, Yohei; Kalbas, Yannik; Halvachizadeh, Sascha; Teuben, Michel; Cesarovic, Nikola; Weisskopf, Miriam; Hülsmeier, Andreas; Hornemann, Thorsten; Cinelli, Paolo; Pape, Hans-Christoph; Pfeifer, Roman (European Journal of Trauma & Emergency Surgery, 2024)
Background: Occult hypoperfusion describes the absence of sufficient microcirculation despite normal vital signs. It is known to be associated with prolonged elevation of serum lactate and later complications in severely injured patients. We hypothesized that changes in circulating lipids are related to responsiveness to resuscitation. The purpose of this study is investigating the relation between responsiveness to resuscitation and lipidomic course after poly trauma. Methods: Twenty-five male pigs were exposed a combined injury of blunt chest trauma, liver laceration, controlled haemorrhagic shock, and femoral shaft fracture. After 1 h, animals received resuscitation and fracture stabilization. Venous blood was taken regularly and 233 specific lipids were analysed. Animals were divided into two groups based on serum lactate level at the end point as an indicator of responsiveness to resuscitation (<2 mmol/L: responder group (R group), ≧2 mmol/L: occult hypoperfusion group (OH group)). Results: Eighteen animals met criteria for the R group, four animals for the OH group, and three animals died. Acylcarnitines showed a significant increase at 1 h compared to baseline in both groups. Six lipid subgroups showed a significant increase only in R group at 2 h. There was no significant change at other time points. Conclusions: Six lipid groups increased significantly only in the R group at 2 h, which may support the idea that they could serve as potential biomarkers to help us to detect the presence of occult hypoperfusion and insufficient resuscitation. We feel that further study is required to confirm the role and mechanism of lipid changes after trauma.